Nucleotide sequence and analysis of the coliphage T3 S-adenosylmethionine hydrolase gene and its surrounding ribonuclease III processing sites. - Hughes, J A (1987)
To understand better the characteristics of the coliphage T3 S-adenosyl-L-methionine (AdoMet) hydrolase (AdoMetase, E.C. 3.3.1.2) and its expression in phage-infected Escherichia coli, we determined the DNA sequence of the cloned gene and its surrounding ribonuclease (RNase) III mRNA transcript processing sites. The AdoMetase gene contains two in-frame protein translation initiation sites specifying peptides 17105 and 13978 daltons in size. Both proteins terminate at the same ochre codon making the shorter peptide identical to the carboxy terminal 82% of the 17 kd protein. Our data explain the existence of two AdoMetase-related peptides in preparations of the purified enzyme as well as identify sequences that might serve to regulate the enzyme's expression. Comparisons between this T3 sequence and the homologous 0.3 gene region of the closely related coliphage T7 show both the nucleotide and amino acid sequences to be unrelated. The RNase III mRNA processing sites that bracket these genes in T3 and T7 are highly conserved in both their primary and secondary structures.